WATER, FIRE, WIND, AND SOIL AS THE IDEAS OF CREATION OF GRAPHIC ART WORK - adi, sigit purnomo; Sukerta, Pande Made; Marianto, M. Dwi; Hadi, Sri (ISI Press Institut Seni Indonesia Surakarta, 2020)
The creation of this graphic work considers the reciprocal relationship between art and the environment as well as its preservation with an Eco Art perspective. The creation of this Eco-Graphic work uses the Artistic Creation approach which includes experimentation, reflection, and formation (art structure). This Eco Graphic work is inspired by the stimulation of creating water, fire, wind and soil in Javanese philosophy which is then processed in such a way that it becomes a graphic art work in an eco art perspective. Through inner research or inner wandering, the creator is able to visualize the work of Eco Graphic after discovering triangles, circles and lines as the main motive with the abstract expressionism model.